A Green HPLC Method for Determination of Nine Sulfonamides in Milk and Beef, and Its Greenness Assessment with Analytical Eco-Scale and Greenness Profile. (4th June 2020) - Duan, Xiaoyun; Liu, Xiaofeng; Dong, Yue; Yang, Jing; Zhang, Jing; He, Shujuan; Yang, Fatang; Wang, Zhen; Dong, Yuming
Abstract: Background: Sulfonamides have been widely used in the prevention and clinical treatment of bacterial diseases in livestock and poultry. The use of sulfonamides increases the risk of veterinary drug residues in animal derived foods. The traditional reversed phase liquid chromatography methods for sulfonamides residues detection in animal derived foods have the problem of high consumption of organic solvents. Objective: The aim of this study was to establish a green high-performance liquid chromatography method for the detection of sulfonamides residues in different animal-origin foods. Method: The sample extraction solutions were purified by the Agela Cleanert PEP-2 cartridge and analyzed by the high-performance liquid chromatography method using ethanol as the green alternative solvent. Results: The proposed method was validated in terms of linear range (20–1000 μg/kg), limit of detection (3.0–12.3 μg/kg), limit of quantitation (10–43 μg/kg), accuracy (80.7–101.3%), and repeatability and reproducibility (RSD <5.9% and RSD <8.5% respectively). Conclusions: The proposed method is an environmentally friendly, sensitive and reliable high-performance liquid chromatography method for simultaneous determination of sulfonamide residues in animal-origin foods. Highlights: In this work, we firstly developed a green high-performance liquid chromatography method for simultaneous determination of the residues of nine sulfonamides in milk and beef with ethanol as the green alternative solvent.